1996
DOI: 10.1177/105268469600600105
|View full text |Cite
|
Sign up to set email alerts
|

Using Cohorts as a Means for Developing Transformational Leaders

Abstract: The practice of using cohorts in educational leadership programs is examined from conceptual and practical viewpoints. Suggestions for developing cohorts are followed by discussion of the effects of cohorts on students, faculty, educational programs, and systems. Lastly, this paper takes a look at the potential of using the cohort concept as a vehicle for the development of transformational leaders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 3 publications
2
18
0
Order By: Relevance
“…The strong interpersonal relationships that develop in cohorts through group collaboration, community, and affiliation can influence students' leadership development (Basom et al, 1996(Basom et al, /1997Herbert & Reynolds, 1992;Hill, 1995;Leithwood et al, 1995;Milstein & Krueger, 1993). In most cases, they identified many of the same issues-interpersonal relationships, skill and knowledge development, programmatic advantages, and professional contacts and networking-that other scholars have speculated about or have discovered in their own investigations of cohorts.…”
Section: The Relationship Of This Study To Earlier Studiesmentioning
confidence: 99%
“…The strong interpersonal relationships that develop in cohorts through group collaboration, community, and affiliation can influence students' leadership development (Basom et al, 1996(Basom et al, /1997Herbert & Reynolds, 1992;Hill, 1995;Leithwood et al, 1995;Milstein & Krueger, 1993). In most cases, they identified many of the same issues-interpersonal relationships, skill and knowledge development, programmatic advantages, and professional contacts and networking-that other scholars have speculated about or have discovered in their own investigations of cohorts.…”
Section: The Relationship Of This Study To Earlier Studiesmentioning
confidence: 99%
“…As the Council for Adult and Expe riential Learning/American Council of Education 0993) re port on Adult Degree Programs identifies, cohot1 groups pro vide a model that is relatively inexpensive and administratively manageable. Of late, however, more educators are also realiz ing that cohort groups enhanced learning potential (Barnett & Muse, 1993;Basom et al, 1996;Brooks, 1998;Reynolds & Hebert, 1995).…”
Section: Cohort Groupsmentioning
confidence: 95%
“…Of particular interest was the way the best practice findings of the Whitaker et al study (2004) mirrored the best practices identified in other studies that focused on leadership development partnerships between school districts and universities (e.g., Basom, Yerkes, Norris, & Barnett, 1996;Glasman & Glasman, 1997;Jackson & Kelley, 2002;Orr, 2006;Teitel, 2006). It was clear from reading the few studies that were available that school district-university partnerships that focused on quality curriculum and instruction as elements of their leadership-preparation programs; cohort learning (vs. an individualized approach); integral involvement of school district(s) in the development and delivery of curriculum and instruction in the leadership programs; provision of an excellent internship program with committed mentors; and a commitment to program participants through advising and other forms of assistance were among the more successful partnerships.…”
mentioning
confidence: 86%
“…In addition to that best practice, each program used a cohort model for the delivery of its instructional program based on the high quality curriculum; each had strong internship programs that fit their program delivery models; and each implemented an advisory model that also seemed to fit their scheme of program delivery. Although all of the former findings for the three partnerships were considered to be best practices in the research literature (e.g., Davis et al, 2005;Orr, 2006;Preis et al, 2007;Teitel, 2006) and earlier studies (Basom et al, 1996;Glasman & Glasman, 1997;Jackson & Kelley, 2002), the three partnerships were exemplary in (a) the development of high quality curriculum and delivery of instruction and (b) the commitment of the partnerships to provide support to the participants through advising and other forms of assistance.…”
Section: District-university Collaborationsmentioning
confidence: 97%